Upaya Penyelesaian Kasus Pembunuhan Akibat Sengketa Tanah Ulayat Melalui Mekanisme Hukum Adat di Wilayah Adonara Kabupaten Flores Timur - Maria Penaten Peran; Karolus Kopong Meda; Andrianus Djara Dima (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
One of the traditional cultures that is currently still practiced by the Adonara community is the fight war. The story of the battle war in the Adonara Area, East Flores Regency, is the battle between Lewobunga Village and Lewonara Village. This rivalry war was triggered by the ownership of customary land rights between Lewobunga Village and Lewonara Village, where the Lewobunga Village Community inaugurated Riangbunga Hamlet Lewobunga Village heard the inauguration the Lewonara Village people did not agree and began to carry out their act of disacceptance by attacking the Lewobunga Village community. So there was a prolonged war and conflict that caused many casualties. This study found several things: (1) The factors that cause the occurrence of murder cases due to customary land disputes are: unclear land boundaries, differences in historical narratives, lack of recognition of land ownership, war revenge and lack of attention from the local government. (2) Settlement efforts carried out by traditional leaders by gathering the entire community and inviting traditional leaders in neighboring villages in the Kiwangona area to perform the traditional ritual of bau lolon to pray that the fight war will not be repeated by declaring the reket kame lo'oko (weapons of war are released) with this statement the community expresses their hearts by declaring that the war will stop or there will be no more wars and this traditional ritual is sacred.